2019
DOI: 10.3390/jcm8050587
|View full text |Cite|
|
Sign up to set email alerts
|

Fast Tac Metabolizers at Risk—It is Time for a C/D Ratio Calculation

Abstract: Tacrolimus (Tac) is a part of the standard immunosuppressive regimen after renal transplantation (RTx). However, its metabolism rate is highly variable. A fast Tac metabolism rate, defined by the Tac blood trough concentration (C) divided by the daily dose (D), is associated with inferior renal function after RTx. Therefore, we hypothesize that the Tac metabolism rate impacts patient and graft survival after RTx. We analyzed all patients who received a RTx between January 2007 and December 2012 and were initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
100
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(108 citation statements)
references
References 25 publications
5
100
3
Order By: Relevance
“…reported in a large US-based single-center study that the tacrolimus metabolism rate, defined as the concentration-to-dose ratio (CDR), does not have an impact on biopsy-proven acute rejection as previously shown in kidney transplant recipients. [1][2][3] In contrast to our results, they observed a higher mortality rate in nonrapid metabolizers (NRM) compared to rapid metabolizers (RM). 2 Although estimated glomerular filtration rate values were lower at several time points in RMs compared to NRM, they vote against CDR-based tailoring of the tacrolimus therapy.…”
contrasting
confidence: 99%
“…reported in a large US-based single-center study that the tacrolimus metabolism rate, defined as the concentration-to-dose ratio (CDR), does not have an impact on biopsy-proven acute rejection as previously shown in kidney transplant recipients. [1][2][3] In contrast to our results, they observed a higher mortality rate in nonrapid metabolizers (NRM) compared to rapid metabolizers (RM). 2 Although estimated glomerular filtration rate values were lower at several time points in RMs compared to NRM, they vote against CDR-based tailoring of the tacrolimus therapy.…”
contrasting
confidence: 99%
“…Recently, Jouve et al [3] showed in a large retrospective singlecenter study that the C/D ratio was in contrast to the CYP3A5 genotype strongly associated with outcomes after renal transplantation (RTx). They used a C/D ratio cutoff of 1.05 µg/l 9 1/mg, which we used to guide risk stratification of RTx patients, as a low C/D ratio (fast Tac metabolism) is associated with, for example, an increased calcineurin inhibitor nephrotoxicity rate, a lower estimated glomerular filtration rate (eGFR), and five-year patient and overall graft survival [5,9].…”
Section: Dear Editorsmentioning
confidence: 99%
“…
There is an emerging interest in the tacrolimus metabolism rate as it is linked to outcomes after transplantation [1][2][3][4][5][6][7]. We and others propose the concentration-to-dose (C/D) ratio as a simple surrogate for the individual tacrolimus (Tac) metabolism rate [5,8,9]. Recently, Jouve et al [3] showed in a large retrospective singlecenter study that the C/D ratio was in contrast to the CYP3A5 genotype strongly associated with outcomes after renal transplantation (RTx).
…”
mentioning
confidence: 99%
See 2 more Smart Citations